Structural and functional characteristics of liver cells depends of SHF-radiation - Kaiyrbekova, K. K.; Medeshova, A. T.; Naurisov, N. N.; Baimagambetova, D. D.; Sakenova, M. N.; Omarova, L. S. (Experimental biology, 2015)
It has been finded that structural and functional changements of liver cells depends of SHF-radiation density and duration. In the beginning while radiation at warming position a synthetic activity increases and than decreases, a hydropic dystrophy of cells developes